Molecular Cloning and Characteristics of Allele Variants (GATA) n , the Microsatellite Locus Du281 of Parthenogenetic Caucasian Rock Lizard (Darevskia unisexualis) Genome - Korchagin, V. I.; Churikov, N. A.; Tokarskaya, O. N.; Sevast'yanova, G. A.; Filippovich, Yu. B.; Ryskov, A. P. (Doklady. Biochemistry and biophysics, 2004)
(ProQuest: Abstract omitted; see image)[PUBLICATION ABSTRACT]